Carotid Atherosclerosis, Endothelial Disfunction, and Arterial Stiffness in Young and Middle-Aged Men with Coronary Artery Disease - Sergey Kozlov; Tatyana Balachonova; Heda Machmudova; Marya Tripoten; Marina Andreevskaya; Anatoly Rogoza; Valery Kuharchuk (International Journal of Vascular Medicine, 2012)
Background. To assess structural and functional status of the arteries in young and middle-aged men with recently developed CAD. Methods and Results. A total of 78 men aged 28 to 50 years underwent carotid ultrasound, endothelial function, and arterial stiffness measurements. Angiographically proven CAD was present in 49 patients. Carotid plaques were present in 45 (91.8%) patients with CAD and in 8 (27.6%) men without CAD (𝑃<0.001). Patients with CAD more often had multiple plaques (86.7% versus 13.8%, 𝑃<0.001). The prevalence of carotid intima-media thickness (IMT) ≥0.9 mm and of abnormal brachial artery flow-mediated dilatation (FMD) was not differing in both groups. The mean aortic pulse wave velocity (PWV) was 6.8±1.3 m/s for patients with CAD and 5.8±0.9 m/s for subjects without CAD (𝑃<0.001). Aortic PWV above the 75th percentile of the “normal” samples was found in 26 (53.1%) patients with CAD and in 7 (24.1%) subjects without CAD (𝑃=0.02). Aortic PWV was related to the severity of CAD. Conclusions. Carotid plaques and increased aortic PWV may be more powerful predictors of the occurrence of CAD in young and middle-aged men, than the presence of increased carotid IMT and abnormal brachial artery FMD.